2015
DOI: 10.3109/08880018.2015.1085936
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Burkitt Lymphoma: Long-term Outcome in 87 Patients Who Presented With Paraplegia in Cameroon

Abstract: The reported long-term outcome of endemic Burkitt lymphoma (eBL) patients who present with paraplegia is largely unknown. Records of BL patients treated with comparable short-interval cyclophosphamide chemotherapy schedules between 2004 and 2014 at three Baptist mission hospitals in Cameroon were reviewed. Survivors were followed up and examined at home or in hospital. Eighty-seven of 948 (9.2%) patients had paraplegia at diagnosis. The survival rate in eBL patients with paraplegia at diagnosis was 33% (n = 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…Overall survival was 52% for this study population, with a male:female ratio of 1.5:1, similar to that in other reports . The mean age of 8.2 years was slightly older than that in some reports, but consistent with previous studies in Northwest Cameroon . The Psychosocial Issues Working Group of the International Paediatric Oncology Society suggested that refusal, non‐compliance and abandonment were major issues influencing overall survival in low‐ and middle‐income countries .…”
Section: Discussioncontrasting
confidence: 79%
“…Overall survival was 52% for this study population, with a male:female ratio of 1.5:1, similar to that in other reports . The mean age of 8.2 years was slightly older than that in some reports, but consistent with previous studies in Northwest Cameroon . The Psychosocial Issues Working Group of the International Paediatric Oncology Society suggested that refusal, non‐compliance and abandonment were major issues influencing overall survival in low‐ and middle‐income countries .…”
Section: Discussioncontrasting
confidence: 79%
“…Two of the reports addressed awareness, 7,11 10 addressed diagnosis, registration, and epidemiology, 5,[12][13][14][15][16][17][18][19][20] 18 addressed management and outcomes, 7,14,16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] four addressed supportive care, [36][37][38][39] five addressed palliative care, [40][41][42][43][44] four addressed advocacy and F I G U R E 1 Map of Cameroon showing location of dedicated pediatric oncology units partnerships, 35,37,45,46 and one addressed T&CM 39 (Supporting Information File S1).…”
Section: Resultsmentioning
confidence: 99%
“…Additional follow-up has been done by means of outreaches and by using mobile phones to establish specific outcomes. 26 survival of 61% for BL at the above-mentioned three Baptist Hospitals, two of which were in the Northwest Region. 22,30 This was the first report on BL survival specific to Cameroon.…”
Section: Management and Outcomes Of Common Childhood Cancersmentioning
confidence: 93%
See 1 more Smart Citation
“…Current and former personnel from MBH have successfully collaborated on numerous national and international research investigations. [62][63][64][65][66][67] The pre-existing infrastructure present at both sites, combined with personal knowledge and established relations between study sites, allows for study feasibility and anticipated success.…”
Section: Discussionmentioning
confidence: 99%